2015
DOI: 10.1080/13670050.2015.1037715
|View full text |Cite
|
Sign up to set email alerts
|

Play to learn: self-directed home language literacy acquisition through online games

Abstract: Home language literacy education in Australia has been pursued predominantly through Community Language Schools. At present, some 1,000 of these, attended by over 100,000 school-age children, cater for 69 of the over 300 languages spoken in Australia. Despite good intentions, these schools face a number of challenges. For instance, children may lack motivation and perceive after-hours schooling as an unnecessary burden. Trained teachers and suitable teaching materials are often not available. Moreover, not eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
(16 reference statements)
0
14
0
7
Order By: Relevance
“…In the questionnaire, 66% of parents reported that their children were interested in computer games, 56% were interested in web-based (browser) games, and 82% of children were interested in mobile games and apps (with 65% of parents reporting such interest in themselves). This represents a significant proportion, echoing findings by Eisenchlas, Schalley, and Moyes (2016). Simultaneously, 78% of parents reported that their child was interested in the heritage language, and 75% of parents believed that apps and games could motivate their child to learn the heritage language.…”
Section: Interest In Technologymentioning
confidence: 64%
See 3 more Smart Citations
“…In the questionnaire, 66% of parents reported that their children were interested in computer games, 56% were interested in web-based (browser) games, and 82% of children were interested in mobile games and apps (with 65% of parents reporting such interest in themselves). This represents a significant proportion, echoing findings by Eisenchlas, Schalley, and Moyes (2016). Simultaneously, 78% of parents reported that their child was interested in the heritage language, and 75% of parents believed that apps and games could motivate their child to learn the heritage language.…”
Section: Interest In Technologymentioning
confidence: 64%
“…Research among families who speak more than one language is situated against a complex background which refers variously to: immigrant families (Szecsi and Szilagyi 2012;Rumbaut and Portes 2001), bilingualism or multilingualism (Baker 2011) plurilingualism (Prasad 2013), home language (Eisenchlas, Schalley, and Moyes 2016) and heritage language (Cho and Krashen 2000;Szecsi and Szilagyi 2012). Throughout this paper, the term heritage language' is used, since the vast majority of families had views of the 'heritage language' that aligned with Blackledge and Creese's (2010) interpretation, namely a minority language not spoken by the majority within the community or country, with both language and culture being passed down the generations.…”
Section: Defining Heritage Languagementioning
confidence: 99%
See 2 more Smart Citations
“…Although, in each period, there was one treatment group differing significantly from the control group, the treatment groups always had better sound recognition performance than the control group, as shown in Figure . Therefore, the results are promising in that Kes Sesi can be useful in self‐supported learning circumstances with little adult input, such as home language literacy education (Eisenchlas et al, ; Rominus & Lyytinen, ). Especially by adhering to the national norms on categorization, it can also be useful in attended learning environments as a self‐paced practice tool as in any case, game playing groups surpass the nongaming group.…”
Section: Discussionmentioning
confidence: 99%